Peran Mahasiswa Dalam Memajukan UMKM Dengan Pengembangan Design Packaging Produk Toko Kue UD.Pawon Kue Rungkut Surabaya Melalui Wirausaha Merdeka - Shevilla Chourulbia; Ute Chairuz M. Nasution (Politeknik Kampar, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. They are not only the main driver of economic growth but also create jobs. In this era of globalization, students have a great opportunity to play an active role in advancing MSMEs, especially through the Independent Entrepreneurship program. This journal discusses the role of students in developing product packaging design at the UD.Pawon Kue Cake Shop, Rungkut Surabaya, as part of the program. The type of method used is descriptive research with a qualitative approach. Descriptive research is a form of data collected in the form of words, images, and not numbers. Qualitative research is research that aims to understand the phenomena experienced by research subjects such as behavior, perceptions, motivations, actions, and so on by means of descriptions in the form of words and language, in a special natural context, and utilizing various natural methods. (Moleong in Anas, 2021). All the data in this research was obtained through literature study by analyzing every reading presented by previous researchers and also the results of practical field work carried out for 2 months at Diva Digital Marketing. The research results show that the role of students in advancing MSMEs by developing packaging designs for cake shop products has a positive impact. Through close collaboration between students and cake shop owners, improvements can be seen in several critical aspects. In the context of developing product packaging designs for cake shops, the role of students proves themselves as a key element in advancing MSMEs. Collaboration between students and cake shop owners not only creates innovative design breakthroughs, but also has a profound positive impact on the business performance and sustainability of cake shops. Through their creativity, students succeeded in creating product packaging designs that were not only aesthetically attractive but also reflected the cake shop's brand identity. This provides a significant competitive advantage, differentiates the product from competitors and attracts consumer attention. Thus, this collaboration contributes to the creation of a strong brand image and higher product appeal.